The Shackle of Patriarchal Culture Toward the Position of Batak Toba Women as Reflected in "Nyawa Sisa" by Sebastian Partogi - Tantri, Agra Liz; Asmarani, Ratna (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research examines social conflict related to the patriarchal culture in Batak Toba society and describes how patriarchal culture discriminates, weakens, and shackles Batak Toba women as reflected in the short story entitled "Nyawa Sisa" by Sebastian Partogi. The writer conducted library research using contextual methods combined with the sociology of literature to analyze the social issues in this short story. The results show how "Nyawa Sisa" reflects that the patriarchal culture indirectly oppresses and discriminates against women. Men dominate women physically and non-physically, both in the personal and social aspects. Men with special privileges often use their power to commit violence against women and make them the second class.